The use of halloysite clay and carboxyl-functionalised multi-walled carbon nanotubes for recombinant LipL32 antigen delivery enhanced the IgG response - Hartwig,Daiane D (2015)
We studied the feasibility of using halloysite clay nanotubes (HNTs) and carboxyl-functionalised multi-walled carbon nanotubes (COOH-MWCNTs) as antigen carriers to improve immune responses against a recombinant LipL32 protein (rLipL32). Immunisation using the HNTs or COOH-MWCNTs significantly increased the rLipL32-specific IgG antibody titres (p < 0.05) of Golden Syrian hamsters. None of the vaccines tested conferred protection against a challenge using a virulent Leptospira interrogans strain. These results demonstrated that nanotubes can be used as antigen carriers for delivery in hosts and the induction of a humoral immune response against purified leptospiral antigens used in subunit vaccine preparations.